The Impact of Palestine's Accession to The World Trade Organization - Mohammad Basil Jarrar; Diaa Nader Awad (International Journal of Law Research and Studies, 2025)
Purpose: The study aimed to evaluate the positive and negative impacts that might result from Palestine's accession to the World Trade Organization (WTO) if it does, and accordingly express an opinion or position based on weighing the positives over the negatives, or vice versa, in the event of accession. This is achieved by clarifying the positions of supporters and opponents of joining this organization. Methodology: The researcher used the descriptive and analytical approach in the study, where the study began by describing the reality of the situation regarding the conditions for accession to the WTO, and accordingly analyzing the difficulties facing Palestine in its efforts to join it. It also clarified the positive and negative impacts that might result from this accession, and analyzed them through the positions of supporters and opponents of this accession. Findings: The study concluded that the WTO, like other organizations that seek to open the markets of developing countries to developed countries for exploitation, would be difficult for Palestine to join while it lacks even the slightest form of control over the border crossings. Palestine is also not legislatively or economically ready to join and compete with developed countries, or even keep up with them. Compliance with WTO standards and regulations also requires adjustments to Palestinian local industries regarding raw materials and quality, a challenge for small and less developed industries in Palestine. Furthermore, increased competition from imported agricultural products will pose a threat to Palestinian farmers, as they struggle to meet the strict quality and safety standards imposed by the WTO. Furthermore, removing trade barriers will expose the Palestinian agricultural sector to price fluctuations and global market fluctuations. Recommendations: The study recommends that the Palestinian Authority refrain from submitting new accession applications to the WTO until all obstacles and difficulties facing it are overcome. It is also necessary to find a way out of the Paris Protocol, signed with the occupying state. Efforts should also be intensified to support Palestinian farmers, support national institutions and factories, and take all appropriate measures by responsible authorities to support the national economy.
Keywords: World Trade Organization; Paris Protocol; Positive effects; Negative effects; Supporters; Opponents